Clinical profile of first 100 cases of COVID-19 in a COVID-dedicated hospital of Bangladesh (BIRDEM Medical Journal, 2020)
Background: The novel corona virus has been identified as the cause of respiratory illness in Wuhan, Hubei province, China, since December, 2019. It has spread almost all the countries and areas (212) in world. Due to distinct demographics of infection, variation of case fatality and clinical presentation in different countries, the knowledge of demographic distribution and analysis of clinical profile from this study would help for patient management of COVID-19 till the invention of specific drug and vaccines. We aimed to analyze the clinical profile of fist 100 cases of COVID-19 admitted in a teaching hospital.Methods: In this observational study, RT-PCR confirmed first 100 hospitalized COVID-19 cases, admitted in Mugda Medical College Hospital were included. With well informed consent, a structured questionnaire was fulfilled during the time of hospital stay. Data were analyzed with clinical outcome, hospital stay, clinical staging and comorbidity of admitted patient from 20th March to 10th April.Results: Among the total participants, male were predominate (59%). Age groups were ranging from 9 to 80 years and mean age was 43 years. Common symptoms were fever (91%), cough (33%), dyspnea (41%), sore throat (12%), diarrhea (12%) and myalgia (2%). Mild cases (53%) were common, followed by moderate (31%), severe (13%) and critical (3%). Average hospital stay was 11 days. Common comorbidities were diabetes mellitus (21%), hypertension (17%), chronic kidney disease (11%), bronchial asthma (8%), stroke (3%) and ischaemic heart disease (2%).Conclusion: Distinct demographic presentation with age variability, clinical presentation with variable fatality in different countries may help the further steps taken by the policymaker of low resource country for the prevention of infection and management of COVID-19.Birdem Med J 2020; 10, COVID Supplement: 18-22